Musculoskeletal Health in Women - Mody, Elinor; Matzkin, Elizabeth; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
Musculoskeletal Health in Women aims to provide fitness advice tailored to women. As women are more prone to specific injuries than men are, due to differences in hip and knee anatomy as well as hormonal differences, this book will provides a fully-illustrated and comprehensive overview of all aspects including energy availability (which is affected by eating disorders), osteoporosis, and menstrual function. Its multidisciplinary approach ensures that expertise is provided from disciplines such as psychiatry, physiatry, endocrinology, nutrition, rheumatology, orthopedics, physical therapy and radiology. Written by authors who have extensive experience working with women athletes, Musculoskeletal Health in Women addresses a full spectrum of issues related to the musculoskeletal health of women. It is of primary interest to women athletes and women embarking on a fitness regimen. Health professionals working in this area would also invariably benefit from the advice and guidance provided within these pages.
1. The Female Athlete Triad -- 2. Nutritional Recommendations for the Young and Aging Female -- 3. Women$1 (Bs Bone Health: Breathing Life into the Skeleton -- 4. Upper Limb Nerve Entrapment Syndromes -- 5. Lower Limb Nerve Entrapment Syndromes -- 6. Osteoarthritis and Gender-Specific Joint Replacement -- 7. Nutraceuticals: An Alternative for Osteoarthritis Management -- 8. Alternative Exercixe for Women.s
Keywords: Medicine; Orthopedics; Sports medicine; Medicine & Public Health; Sports Medicine; Orthopedics